Perancangan Sistem Informasi Penjualan pada UD. Kripik Singkong Riziby Berbasis Website (Web) - Andaresta, Deka; Sutrisno, Sutrisno; Polewangi, Yudi Daeng (INCODING: Journal of Informatics and Computer Science Engineering, 2023)
UD. Kripik Singkong Riziby is a business in various variants of cassava chips sale. The variants are Balado, Sweet Spicy, Original, and Tela-tela cassava chips that the system used by UD. Kripik Singkong Riziby is still using marketing facilities from facebook because they don’t have e-commerce yet, so it’s a problem in the Trading Business sales system. By using the facebook facility as a sales tool, the scope of sales and promotion is still tiny because only people who are affiliated with UD. Kripik Singkong Riziby’s Facebook account only. The study aimed to know how to create and apply a website-based sales system to assist marketing and income at UD. Kripik Singkong Riziby. For this reason, it was necessary to design a sales system, namely e-commerce. Developing an e-commerce web-based marketing system is beneficial to expand the scope of marketin, promoting, and facilitating users in transactions as well as increasing revenu. The author designed a sales information system for UD. Kripik Singkong Riziby was web-based e-commerce and implemented this information system at UD. Kripik Singkong Riziby. The website design produced in this study is at https://ud-keripiksingkongriziby.m48g.com.